Influence of heat treatment on the sorption and solubility of direct composite resins - Gabrielle Ribeiro Lima Muniz; Erick Miranda Souza; Carolina Carramilo Raposo; Ivone Lima Santana (Wolters Kluwer Medknow Publications, 2013)
Context: Heat treatment allows the use of direct composite resins for fabrication of inlays/onlays restorations because it improves some mechanical and physical properties. Aim: The aim of this study is to analyze the influence of heat treatment on the water sorption and solubility of direct composite resins compared with an indirect composite resin. Materials and Methods: A total of 50 cylindrical specimens were fabricated (6 mm diameter × 2 mm high) and divided into five groups (n = 10): G1 (FillMagic without heat treatment-control 1), G2 (heat-treated FillMagic), G3 (P60 without heat treatment-control 1), G4 (heat-treated P60) and G5 (indirect resin Epricord-control 2). After fabrication, the specimens were placed in a desiccator containing silica gel and maintained at 37°C for 24 h. This cycle was repeated until a constant weight was achieved (m 1 ). Following, the specimens were stored in individual flasks containing 2 ml of distilled water in an oven at 37°C. The specimens were weighed after intervals of 1, 7 and 21 days of immersion in water (m 2 ). After 21 days of storage in water, the specimens were once again desiccated until a constant weight was achieved (m 3 ). The mean diameter and thickness of specimens were obtained using a digital pachymeter. Statistical Analysis Used: Two - way analysis of variance and Tukey's test were used to compare the sorption and solubility (α = 0.05). Results: The type of resin significantly influenced the sorption (P = 0.01) and solubility (P = 0.00). The heat treatment also significantly influenced the sorption (P = 0.026) and solubility (P = 0.01). Conclusion: It was concluded that the heat treatment is an additional curing method that improves strength to the sorption and solubility of composite resins.